Successful Case-based Reasoning Applications - Montani, Stefania.; Montani, Stefania. (Studies in Computational Intelligence,, 2010)
Case-based reasoning offers tremendous advantages over other AI based techniques in all those fields where experiential knowledge is readily available. This research book presents a sample of successful applications of case-based reasoning. The contributions include: • Introduction to case-based reasoning • Case-based reasoning for medical and industrial support systems • Industrial knowledge management applications • Decision making in small and medium enterprises • Heterogeneity in ontological CBR systems • The adaptation problem in medical case-based reasoning systems • Prototype-based classification in unbalanced biomedical problems • Case-based ranking for environmental risk assessment • Recipe advisor and menu creator The book is directed to the application engineers, scientists, professors and students who wish to develop successful case-based reasoning applications.